2022
DOI: 10.1111/jam.15418
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antiviral activity of Thymbra spicata L. extract on bovine respiratory viruses (BCoV, BPIV-3, BRSV, BVDV and BoHV-1)

Abstract: Aims: Viral pathogens are the primary agents in bovine respiratory disease cases, and there is no direct effective antiviral drug application. Thymbra is a genus of oregano commonly found in Turkey. The primary component (34.9%) of the extract obtained from Thymbra spicata L. is the carvacrol which is used in traditional medicine. This study evaluates the potential antiviral activity and inactivation efficiency of T. spicata L. extract against bovine respiratory viruses, including BCoV, BPIV-3, BRSV, BVDV and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Treatment of these viruses with 1.5% T. spicata L. extract resulted in a reduction of infectious virions by 99.44%, 100.0%, 94.38%, 99.97% and 99.87% for BCoV, BPIV‐3, BRSV, BVDV and BoHV‐1, respectively. The extract of T. spicata L. also demonstrated strong dose‐dependent inhibition of viral replication in vitro for all the mentioned viruses 31 …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Treatment of these viruses with 1.5% T. spicata L. extract resulted in a reduction of infectious virions by 99.44%, 100.0%, 94.38%, 99.97% and 99.87% for BCoV, BPIV‐3, BRSV, BVDV and BoHV‐1, respectively. The extract of T. spicata L. also demonstrated strong dose‐dependent inhibition of viral replication in vitro for all the mentioned viruses 31 …”
Section: Discussionmentioning
confidence: 89%
“…The extract of T. spicata L. also demonstrated strong dose-dependent inhibition of viral replication in vitro for all the mentioned viruses. 31 Rosmarinic acid, vitexin and gallic acid were found the highest amount in leaf subextract. Rosmarinic acid is a phenolic acid consisting of an ester of caffeic acid and 3,4-dihydroxy phenyl lactic acid and is a bioactive phytochemical that can be found in many plants as ethnomedicines.…”
Section: Quantitative Analysis Of Secondary Metabolitesmentioning
confidence: 92%
“…For laboratory studies, the epithelial cell line Madin Darby Bovine Kidney (MDBK) is commonly used for the in vitro multiplication of BVDV [ 106 , 107 , 108 ], BoHV-1 [ 107 , 109 ], and BoHV-4 [ 110 , 111 , 112 ]. In addition, the susceptibility of primary endometrial cultures to BoHV-4 and BVDV has been reported [ 102 , 113 , 114 ].…”
Section: Challenges and Obstacles In Bovine Embryo-maternal Communica...mentioning
confidence: 99%
“…T. spicata leaves and flowers are used as food ingredients in salad and in tea infusions. Different biological and bio-functional effects have been reported for T. spicata including anti-oxidant and antisteatotic [ 12 ], antihypercholesterolaemic [ 13 , 14 ], antitumoral [ 15 ], antiviral [ 16 ], and antimicrobial [ 17 , 18 , 19 ] activities.…”
Section: Introductionmentioning
confidence: 99%